How to divide the two complex numbers in polar form ?
Let z1 = r1(cos θ1 + i sin θ1 ) and z2 = r2(cos θ2 + i sin θ2 ) be two complex numbers in the polar form.
We can use the formula given below to find the division of two complex numbers in the polar form.
z1/z2 = r1/r2[cos (θ1 - θ2) + i sin (θ1 - θ2)]
Find the trigonometric form of the quotient.
Example 1 :
z1 = 2(cos 30˚ + i sin 30˚)
z2 = 3(cos 60˚ + i sin 60˚)
Solution :
By using the z1/z2 formula, we get
z1/z2 = (2/3)[cos (30˚ - 60˚) + i sin (30˚ - 60˚)]
z1/z2 = (2/3)[cos (-30˚) + i sin (-30˚)]
Example 2 :
z1 = 5(cos 220˚ + i sin 220˚)
z2 = 2(cos 115˚ + i sin 115˚)]
Solution :
By using the z1/z2 formula, we get
z1/z2 = 5/2[cos (220˚ - 115˚) + i sin (220˚ - 115˚)]
z1/z2 = 5/2(cos 105˚ + i sin 105˚)
Example 3 :
z1 = 6(cos 5π + i sin 5π)
z2 = 3(cos 2π + i sin 2π)
Solution :
z1/z2 = 6/3[cos (5π - 2π) + i sin (5π - 2π)]
z1/z2 = 2(cos 3π + i sin 3π)
Example 4 :
z1 = cos (π/2) + i sin (π/2)
z2 = cos (π/4 + i sin (π/4)
Solution :
z1/z2 = cos (π/2 - π/4) + i sin (π/2 - π/4)
Taking the least common multiple, we get
z1/z2 = cos ((2π - π)/4) + i sin ((2π - π)/4)
z1/z2 = cos (π/4) + i sin (π/4)
Simplify. Express answers in both polar form and in rectangular form. Match angle measurement units to the problem, where 0° < θ < 360° or 0 ≤ θ ≤ 2π
Example 5 :
6(cos 𝜋/2 + 𝑖 sin 𝜋/2) ∙ 4(cos 𝜋/4 + 𝑖 sin 𝜋/4)
Solution :
= 6(cos 𝜋/2 + 𝑖 sin 𝜋/2) ∙ 4(cos 𝜋/4 + 𝑖 sin 𝜋/4)
= 6(4) (cos (𝜋/2 + 𝜋/4) + 𝑖 sin (𝜋/2 + 𝜋/4))
= 24 (cos (2𝜋+𝜋)/4 + 𝑖 sin (2𝜋+𝜋)/4)
Polar form :
= 24 (cos (3𝜋/4) + 𝑖 sin (3𝜋/4))
Rectangular form :
= 24 [cos (𝜋-𝜋/4) + 𝑖 sin (𝜋-𝜋/4)]
= 24 [cos (𝜋/4) + 𝑖 sin (𝜋/4)]
= 24 [-√2/2 + 𝑖√2/2]
= 24 [(-√2 + 𝑖√2)/2]
= 12 (-√2 + 𝑖√2)
Example 6 :
5(cos 135 + 𝑖 sin 135) ∙ 2(cos 45 + 𝑖 sin 45)
Solution :
= 5(cos 135 + 𝑖 sin 135) ∙ 2(cos 45 + 𝑖 sin 45)
= 5(2) (cos (135 + 45) + 𝑖 sin (135 + 45))
= 10 (cos 180 + 𝑖 sin 180)
Polar form :
= 10 (cos 180 + 𝑖 sin 180)
Rectangular form :
= 10 (-1 + 𝑖 (0))
= 10(-1)
= -10
Example 7 :
3(cos (3𝜋/4) + 𝑖 sin (3𝜋/4)) ÷ (1/2)(cos 𝜋 + 𝑖 sin 𝜋)
Solution :
= 3(cos (3𝜋/4) + 𝑖 sin (3𝜋/4)) ÷ (1/2)(cos 𝜋 + 𝑖 sin 𝜋)
= 3/(1/2)[(cos (3𝜋/4) + 𝑖 sin (3𝜋/4) ÷ (cos 𝜋 + 𝑖 sin 𝜋)]
= 6[cos ((3𝜋/4) - 𝜋) + 𝑖 sin ((3𝜋/4) - 𝜋)]
= 6[cos ((3𝜋-4𝜋)/4) + 𝑖 sin ((3𝜋-4𝜋)/4)]
= 6[cos (-𝜋/4) + 𝑖 sin (-𝜋/4)]
Polar form :
6[cos (𝜋/4) - 𝑖 sin (𝜋/4)]
Rectangular form :
= 6[cos (𝜋/4) - 𝑖 sin (𝜋/4)]
= 6[(√2/2) - 𝑖 (√2/2)]
= 6[(√2 - 𝑖 √2)/2]
= 3(√2 - 𝑖 √2)
Example 8 :
3(cos (𝜋/6) + 𝑖 sin (3𝜋/4)) ÷ 4(cos 2𝜋/3 + 𝑖 sin 2𝜋/3)
Solution :
= 3(cos (𝜋/6) + 𝑖 sin (3𝜋/4)) ÷ 4(cos 2𝜋/3 + 𝑖 sin 2𝜋/3)
= (3/4)(cos ((𝜋/6)-(2𝜋/3)) + 𝑖 sin ((𝜋/6)-(2𝜋/3)))
= (3/4)[cos ((𝜋/6)-(4𝜋/6)) + 𝑖 sin ((𝜋/6)-(4𝜋/6))]
= (3/4)[cos (𝜋-4𝜋)/6 + 𝑖 sin (𝜋-4𝜋)/6)]
= (3/4)[cos (-3𝜋/6) + 𝑖 sin (-3𝜋/6)]
= (3/4)[cos (-𝜋/2) + 𝑖 sin (-𝜋/2)]
Polar form :
= (3/4)[cos (𝜋/2) - 𝑖 sin (𝜋/2)]
Rectangular form :
= (3/4)[cos (𝜋/2) - 𝑖 sin (𝜋/2)]
= (3/4)[0 - 𝑖 (1)]
= (3/4)(-1)
= -3/4
Example 9 :
4(cos (9𝜋/4) + 𝑖 sin (9𝜋/4)) ÷ 2(cos 3𝜋/2 + 𝑖 sin 3𝜋/2)
Solution :
= 4(cos (9𝜋/4) + 𝑖 sin (9𝜋/4)) ÷ 2(cos 3𝜋/2 + 𝑖 sin 3𝜋/2)
= (4/2)[cos ((9𝜋/4)-(3𝜋/2)) + 𝑖 sin ((9𝜋/4)-(3𝜋/2))]
= 2[cos ((9𝜋-3𝜋)/4)) + 𝑖 sin ((9𝜋-3𝜋)/4))]
= 2[cos (6𝜋/4) + 𝑖 sin (6𝜋/4)]
= 2[cos (3𝜋/2) + 𝑖 sin (3𝜋/2)]
Polar form :
= 2[cos (3𝜋/2) + 𝑖 sin (3𝜋/2)]
Rectangular form :
= 2[cos (3𝜋/2) + 𝑖 sin (3𝜋/2)]
= 2[0 + i(-1)]
= 2(-i)
= -2i
Example 10 :
6(cos (3𝜋/4) + 𝑖 sin (3𝜋/4)) ÷ 2(cos 𝜋/4 + 𝑖 sin 𝜋/4)
Solution :
= 6(cos (3𝜋/4) + 𝑖 sin (3𝜋/4)) ÷ 2(cos 𝜋/4 + 𝑖 sin 𝜋/4)
= 6/2[cos ((3𝜋/4) - (𝜋/4)) + 𝑖 sin ((3𝜋/4) - (𝜋/4))]
= 3[cos (3𝜋 - 𝜋)/4 + 𝑖 sin (3𝜋 - 𝜋)/4]
= 3[cos (2𝜋/4) + 𝑖 sin (2𝜋/4)]
= 3[cos (𝜋/2) + 𝑖 sin (𝜋/2)]
Polar form :
= 3[cos (𝜋/2) + 𝑖 sin (𝜋/2)]
Rectangular form :
= 3[cos (𝜋/2) + 𝑖 sin (𝜋/2)]
= 3[0 + i(1)]
= 3i
Example 11 :
(1/2)(cos (𝜋/3) + 𝑖 sin (𝜋/3)) ÷ 3(cos 𝜋/6 + 𝑖 sin 𝜋/6)
Solution :
= (1/2)(cos (𝜋/3) + 𝑖 sin (𝜋/3)) ÷ 3(cos 𝜋/6 + 𝑖 sin 𝜋/6)
= ((1/2)/3)[cos ((𝜋/3)-(𝜋/6)) + 𝑖 sin ((𝜋/3)-(𝜋/6))]
= (1/6)[cos ((2𝜋-𝜋)/6)) + 𝑖 sin ((2𝜋-𝜋)/6))]
= (1/6)[cos (𝜋/6) + 𝑖 sin (𝜋/6)]
Polar form :
= (1/6)[cos (𝜋/6) + 𝑖 sin (𝜋/6)]
Rectangular form :
= (1/6)[cos (𝜋/6) + 𝑖 sin (𝜋/6)]
= (1/6) [√3/2 + i(1/2)]
= (1/6)[(√3 + i)/2]
= (√3 + i)/12
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Feb 06, 25 09:46 AM
Feb 05, 25 12:22 PM
Feb 05, 25 12:15 PM